The Investment Security of the Country: Strategic Goals and Support Mechanisms - Bondaruk, T. H.; Bondaruk, O. S. (Statistics of Ukraine, 2019)
It is justified that scientific studies of economic security at country level gain higher importance in the conditions of transformation. The processes concerned with the investment security are gaining special significance, because it is an important condition for the sustainable development of a country. An econometric assessment of the data on incoming foreign direct investment in the national economy and Investment Attractiveness Index of Ukraine is performed. The theoretical framework of the investment security and its strategic goals are investigated. The investment security mechanism is defined by the author as the system of organizational, economic, institutional and legal actions with impact on the domestic economic environment, intended to stimulate domestic and foreign investors to sustain the scopes of economic investment capable to guarantee the extended reproduction of the economy, protection of the national economic interests, effective location, prevention and liquidation of the threats to the investment security of a country. The theoretical construction of the investment security mechanism is defined; its underlying theoretical and methodological principles are extended. It is shown that the organizational and economic mechanism for the investment security represents a multilevel hierarchical system of causally linked organizational and economic mechanisms and their typical groups (entities, objects, principles, methods, instruments etc.), and the ways of their interactions that harmonize economic relations (interests) of the government and business entities and the whole society. It is demonstrated that the investment security needs to be based on the following principles: the elaborated strategy; the clearly formulated national economic interests; the classification of threats; the defined set of indicators and their marginal levels; the security assessment; the applications of tools, ways and methods to ensure security; the elaborated strategy of the investment security. The investment security mechanism is implemented with the goal of guaranteeing the national economic interest. It is shown that the next step in the study has to focus on indentifying the risks and threats to the investment security and building the mechanism for protecting the national interests of a country.